(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents analysis of the effect of urea nitrate salt and nitric acid solutions on low-grade phosphorites of Central Kyzylkum and the results of X-ray phase analysis of their products. Changes in the composition of the samples were studied by X-ray phase analysis, the degrees of their crystallinity and amorphousness, relative changes, and particle sizes were calculated. According to the results, data, their analyses and conclusions are presented on a decrease in the content of the crystalline phase in the solid states of low-quality samples of phosphorites subjected to soaking with urea nitrate and nitric acid, and an increase in the content of the amorphous phase by 5-10%, which increases the digestibility of the main nutrient element in phosphorites P2O5 and CaO, MgO.